Learning to teach : primer on teacher education methods - McGregor, Sue L. T. (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"This primer is about learning how to teach. As its name suggests, it provides a basic introduction to what is involved in becoming an effective, efficient, and efficacious educator. The targeted audiences are (a) preservice teachers (PST) (i.e., nonprofessional student teachers enrolled in a university Bachelor of Education degree), (b) early-career (novice) inservice teachers (c) or any educator for that matter who wants to build or bolster their essential foundation for teaching. The primer is unabashedly oriented to a synthesis of the technical (how-to) aspects of teaching because without prowess in these skills, even the most dedicated and committed teacher may not be effective and efficient let alone efficacious. Although teaching is both a science and an art, this primer is about the science of teaching. Other books focus on teaching as inquiry, thinking educators, reflective educators, and the sociocultural/political aspects of teaching. The book adopts a before-during-after class approach. It addresses how to (a) prepare lessons before a class (learning styles, learning objectives, lesson planning, and learning environments); (b) deliver lessons during a class (instructional strategies, questioning strategies, and classroom management); and (c) evaluate learning after the class (student assessment and evaluation strategies, and teacher self-reflection). This basic tool kit is further underscored with details about the larger constructs of (d) developing courses, modules, and units from which daily lessons emerge. Higher level notions of (e) educational philosophies, (f) curriculum theories and (g) curriculum development approaches are also included to illustrate how they, as the educational context, shape teachers' pedagogies"--